Highly efficient WO3–ZnO mixed oxides for photocatalysis. Issue 16 (21st January 2015) - Adhikari, Sangeeta; Sarkar, Debasish; Madras, Giridhar
Abstract : Monoclinic nanocuboid WO3 enhanced the photocatalyst efficiency of quasi nanobelt zinc oxide for dye degradation in the presence of visible light radiation. Abstract : Monoclinic nanocuboid WO3 enhanced the photocatalyst efficiency of quasi nanobelt zinc oxide for dye degradation in the presence of visible light radiation. Combustion synthesized ZnO resulted in a belt-like morphology through in situ cluster formation of near spherical particles but homogenously disperses and strongly adheres to nanocuboid WO3 during physical mixing. Cationic methylene blue (MB) and anionic orange G (OG) undergo degradation through a charge transfer mechanism in the presence of WO3 –ZnO (1 : 9 weight percentage ratio) mixture. The photocatalytic reaction was enhanced due to the reduction in the recombination of photogenerated electron–holes. The high degree of 90% degradation of both dyes is due to the activity of the mixed oxides, which is much higher than that obtained either with WO3 or ZnO individually.